Exercise training ameliorates adrenergic control in spontaneously hypertensive rats. (17th February 2021) - Ferreira Miranda, Munique Tostes; Lemos, Marina Paiva; Sasaki, Jeffer Eidi; Mota, Gustavo R.; Marocolo, Moacir; Sordi, Carla Cristina de; Almeida, Thalles Ramos; Dias da Silva, Valdo José; Neto, Octávio Barbosa
ABSTRACT: The goal of this study was to examine vascular control after sympathetic stimulation by tyramine infusion in hypertensive rats submitted to swimming training. To this end, male rats were assigned to the following groups: sedentary (SN) and trained normotensive (TN), sedentary (SH) and trained hypertensive (TH). Arterial pressure (AP), heart rate (HR), HR variability (HRV), AP variability (APV), and cardiac autonomic function were recorded. Following, infusion of tyramine was administrated. The TN and TH showed a lower resting HR compared with their respective sedentary groups ( p < .05). Pressure levels were less in TH than SH ( p < .05). The TH showed a higher HRV together with a lower APV in comparison to SH ( p < .05). The sympathetic modulation of HRV and APV was lower in TH than in SH ( p < .05). Both trained groups presented an increased parasympathetic modulation of HRV compared with their respective sedentary groups ( p < .05). The TN and TH groups had a higher vagal effect in comparison with their respective sedentary groups ( p < .001). The sympathetic effect was lower in TH than in SH ( p < .001). Pressor and HR responses to tyramine in different doses were attenuated in TH ( p < .001). Further analysis showed a significant association between infusion of tyramine and normalized LF component of HRV (r = 0.84, p < .001), systolic APV (r = 0.58, p < .001) and diastolic APV (r = 0.49, p < .001). In conclusion, exercise training provokes less pressor response variation by tyramine infusion in hypertensive animals suggesting sympathetic nerve endings adjustments and decrease of the vasoconstrictor effect attenuates injury caused by hypertension improving cardiovascular autonomic dysfunction, which can be associated with sympathetic attenuation.